Agricultural research and development role of scientists and technocrats - Barooah, Satya Ranjan 1919- (New Delhi Concept Pub. Co., 1993)
In the Indian context; includes author's reminiscences as an agricultural technocrat.
Includes bibliographical references (p. [173]-176) and index.
Keywords: Agriculture -- Research -- India; Agricultural innovations -- India -- History; Agriculture -- Technology transfer -- India; Agriculturists -- India -- Social aspects